Experimental study on rockburst fragment characteristic of granite under different loading rates in true triaxial condition - Sun, Feiyue; Guo, Jiaqi; Fan, Junqi; Liu, Xiliang (Frontiers in Earth Science, 2022)
In order to study the effect of loading rate on rockburst, an indoor test of single-face fast unloading-three directions and five-face stress-vertical continuous loading is conducted under different loading rates using a new true-triaxial rockburst test system. The entire process of rockburst inoculation-occurrence-development is completely and accurately reproduced. The fragmentation degree, fractal dimension, and Weibull distribution characteristics of rockburst fragments under different loading rates are compared and analyzed. The results indicate that the rockburst ejection failure process can be summarized as four stages: grain ejection, rock spalling into plates, rock shearing into fragments, and rock fragment ejection. Rockburst fragments are mostly coarse-grained, medium-grained, and fine-grained. The macroscopic block characteristics of rockburst fragments reflect the fragmentation degree of rock, and the fragmentation degree of rockburst fragments increases with the loading rate. The fractal dimension shows the same trend with different loading rates, that is, the fractal dimension grows as the loading rate increases. As the loading rate increases, the crack expansion rate accelerates, which aggravates the damage to the rock specimen by decreasing its compressive strength and causing greater fragmentation when the specimen is failed. The loading rate has a significant effect on the energy consumption of rockburst fragments.